History and Traditional Culture of Altai in Context of the Historical Policy of Soviet State of 1920s-1940s: based on the materials of “Siberian Lights” Magazine - E. I. Krasilnikova (Научный диалог, 2020)
The dynamics of the memory policy aimed at forming in the historical memory of the readership of the Siberian Lights Magazine of the 1920s-1940s ideas about the historical past and traditional culture of Altai people is traced in the article. The relevance of the study is due to the growing attention to the features of historical knowledge in the public space, its structuring, the means of conceptual interpretation and the use in the processes of political self-regulation of society at various stages of development. The novelty of the research is seen in the fact that the history of the state policy of memory in relation to the past of Gorny Altai in its substantive and procedural aspects has not yet become the subject of independent scientific research. The contexts and conditions of creating journal representations of the historical past of Gorny Altai are revealed. The list of the authors covering this topic is characterized, as well as the factors that influenced the creation of journal representations of the history of the Altai people. The stages of this representation are established and characterized. It is shown how the memory policy techniques used by the authors of this journal at different stages changed. It is proved that at the stage of the 1920s, the Siberian Lights served as a platform for polemics of historians and subjects of regional politics, relatively independent in relation to the central government. At the second stage of the 1930s - 1940s, the authors of the journal were included, first of all, in the process of implementing the policy of memory of the central authorities.